PÊNDULO ANCORADO EM MINI-IMPLANTES - ANÁLISE EM MODELOS DIGITAIS - Gregolin, Paula Rotoli (2009)
The distalization of upper molars is a treatment option for Class II malocclusion when there is mainly a dentoalveolar involvement. Intraoral devices such as the Pendulum appliance doesn t need patient s compliance. However, they can cause undesirable effects, such as vestibularization of anterior teeth which participate in the anchorage and tipping of the distalized molars. After the appearance of Temporary Anchorage Devices (TADs), such as mini-implants, anchorage could be reached in a predictable and efficient way. Therefore, using a prospective study, dental alterations were evaluated after distalization of upper molars. A modified pendulum appliance supported by two mini-implants was inserted in the palate of 10 subjects (2 female and 8 male, mean age of 14.3 years old). The sample was composed of 20 dental casts digitalized in 3D and obtained in two stages: treatment beginning (T1) and after distalization with 1mm of overcorrection (T2). This enabled to quantify sagital and transversal dental alte rations, besides possible rotation and angulation movements and vertical movements. The results showed that in sagital direction there was an effective distalization, with statistical significance for upper second molars; upper first molars showed a mean measure of 4.34mm and 3.91mm, for right and left side, respectively; right and left second bicuspids showed a mean measure of 2.06mm and 1.95mm, respectively. On the other hand, anterior teeth showed anchorage loss. In transversal direction, the largest increase occurred in posterior teeth area. The rotation, angulation, and vertical movements of upper first molars suggested that there was a mesiobuccal rotation and a distal tipping of these teeth s crowns, for both sides; vertical measures showed that there was a significant movement only for the right first molar, with distal inclination due to distal cusp intrusion. This device showed to be efficient for Class II correction in a mean time of 6.2 months.(AU)